VD_FINDINFO HC / 2011 / 459 vom 26. Mai 2011 - VD Tribunal cantonal (2011)
CONTRAT DE TRAVAIL, RÉSILIATION ABUSIVE | 8 CC, 102 al. 2 CO, 104 al. 1 CO, 328 CO, 335 al. 1 CO, 336 CO, 339 al. 1 CO, 343 al. 4 CO, 37 LJT, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 312 al. 1 CPC (CH), 404 al. 1 CPC (CH)